1996
DOI: 10.1093/oxfordjournals.aje.a008891
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and Modernization in Coastal and Highland Papua New Guinea

Abstract: Previous studies in Melanesians of Papua New Guinea have documented low serum cholesterol concentrations with no age-related rise and a virtual absence of coronary heart disease. However, because of recent reports of the emergence of coronary heart disease in this population, serum lipid concentrations in adults aged > or = 25 years in three coastal (n = 1,489 and three highland (n = 388) village communities at different stages of modernization were examined as part of a survey undertaken in 1991. Total choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 28 publications
4
44
1
2
Order By: Relevance
“…Moreover, diets high in trans fatty acids, which are abundantly present in processed foods, caused abdominal obesity and insulin resistance (Kavanagh, Jones et al 2007). Similar effects of nutrient poor, calorically dense diets have been demonstrated in humans (Hodge, Dowse et al 1995;Tran, Komatsu et al 2001;Hursting, Lavigne et al 2003;Newby, Muller et al 2003). In humans, caloric restriction also retards aging and reduces rates of chronic disease; therefore, this simple measure may also help to reduce risk for neurodegeneration (Qin, Chachich et al 2006;Kim, Nguyen et al 2007;Wang, Fivecoat et al 2010).…”
Section: Western Diet and Insulin/igf Resistance Mediated Neurodegenementioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, diets high in trans fatty acids, which are abundantly present in processed foods, caused abdominal obesity and insulin resistance (Kavanagh, Jones et al 2007). Similar effects of nutrient poor, calorically dense diets have been demonstrated in humans (Hodge, Dowse et al 1995;Tran, Komatsu et al 2001;Hursting, Lavigne et al 2003;Newby, Muller et al 2003). In humans, caloric restriction also retards aging and reduces rates of chronic disease; therefore, this simple measure may also help to reduce risk for neurodegeneration (Qin, Chachich et al 2006;Kim, Nguyen et al 2007;Wang, Fivecoat et al 2010).…”
Section: Western Diet and Insulin/igf Resistance Mediated Neurodegenementioning
confidence: 63%
“…Crosswww.intechopen.com cultural studies have shown that adoption of Western, go-easy lifestyles with reduced physical activity results in higher rates of obesity (Hodge, Dowse et al 1995), and increased obesity correlates with progressive hyperlipidemia (Berns, de Vries et al 1989). In addition, sedentary lifestyles among children lead to increased energy intake in the forms of fat, sweets, salty snacks, and carbonated beverages, and reduced intake of fruits and vegetables (Coon and Tucker 2002).…”
Section: Sedentary Lifestyles Contribute To Brain Insulin/igf Resistancementioning
confidence: 99%
“…A low fasting triglyceride level (ie, Ͻ100 mg/dL) is commonly found in underdeveloped societies and countries at low CVD risk (eg, Africa, China, Greece, and Japan), [361][362][363][364][365][366][367][368][369][370][371][372][373] as contrasted with the United States, where mean levels are Ϸ15% to 30% higher. 6 Consistent with a reduced likelihood of abnormal metabolic parameters (eg, IR) are observational studies and clinical trials 3,232,367,374 -380 that have consistently demonstrated the lowest risk of incident and recurrent CVD in association with the lowest fasting triglyceride levels.…”
Section: Defining Levels Of Risk Per the National Cholesterol Educatimentioning
confidence: 99%
“…Low HDL occurred in 15.9 (14.2; 17.8)% of males and in 8.0 (7.1; 8.9)% of females. (20,5; 27,5); LDL elevado =26,1 (22,4; 29,3); HDL baixo =15,9 (14,2;17,8) e hipertrigliceridemia =27,6 (25,7; 29,5). Para mulheres: hipercolesterolemia =30,0 (27,8; 32,2), LDL elevado =33,1 (30,8; 35,4); HDL baixo =8,0 (7,1;8,9) e hipertrigliceridemia =30,4 (29,0; 31,4).…”
unclassified